Penerapan Konsep Lean untuk Meningkatkan Operasi Warehouse di Industri Manufaktur - M Syahri Nur Afif; Soemarsono Sudarto (Operations Excellence: Journal of Applied Industrial Engineering, 2022)
This paper discusses the application of lean methods in warehouse operations in the manufacturing industry. To meet customer demand, product storage and product delivery activities are the main things to support customer satisfaction. This paper highlights efforts to improve warehouse operations by eliminating waste using value flow mapping (VSM). This study aims to improve all warehouse operations by analyzing and minimizing waste. The current state of VSM represents a waste of the existing system. The proposed improvement to minimize warehouse operational time is by using the lean concept. The observations through current state value stream mapping obtained a total lead time of 550 minutes. After analyzing the waste and planning improvements, it is expected to reduce the lead time to 525 minutes or 4.5%. The value-added time is reduced from 120 minutes to 90 minutes or 25% through mapping the future value flow of warehouse operations.